Estudio multitemporal de los factores sociodemográficos asociados al trastorno mixto ansioso depresivo en los cantones de Macará y Huaquillas, periodo 2018-2021 - Yaguana Collaguazo, Jhoselyn de los Ángeles (2023)
Worldwide, the most common mental disorders are anxiety and depression, among the highest existing comorbidity that causes an incapacity to perform in the different areas of the biopsychosocial environment. Mixed depressive-anxiety syndrome disorder is also frequent in the world population and implies a high economic cost for health. The present research work aims to identify the prevalence and sociodemographic factors associated with this disorder in the border areas of the Southern Region of Ecuador in the cantons of Huaquillas and Macará, through a non-experimental design study of retrospective cross-sectional-mixed, between the years 2018 to 2021, through the Automated Daily Record of consultations and outpatient care (RDCAA) and the Platform for registration of health care (PRAS), granted by the Ministry of Public Health. We conducted the research employing a non-probabilistic sampling with 639 psychological and psychiatric consultations with mixed anxious-depressive syndrome disorder, where we obtained the following results: Macará canton 30.99%, Huaquillas canton: 69.01%. The adult population between 30 and 64 years of age is the most likely to suffer from this disorder. According to sociodemographic characteristics, it is more frequent in women (76.51%) and heterosexual people (71.03%), with mestizo ethnic self-identification. In addition, since these are border areas, we attended Peruvian, Venezuelan, Salvadoran, and Colombian people. These data allowed the formulation of a psychotherapeutic program for the mixed anxiety-depressive disorder